A atuação do bispo Martinho de Braga na organiząão da igreja Galega (segunda metade do século VI) - Fiorot, Juliana Bardella [UNESP] (My University, 2014)
The period after the fall of the Western Roman Empire was presented as a challenge to the Catholic Church. With the barbarian invasions, together with the geopolitical changes of territory and entrenched paganism especially among rural populations, the Church lost much of its prestige and found itself at a crossroad: it was necessary to adapt to new times or succumb to the recent changes. Therefore we intend to address the relations among Church, Popular Religiosity and Suebian Monarchy in Galicia during the second half of the sixth century. Based on a review and analysis of research literature that was selected for this study, we will give special attention to the challenges faced by the Church in order to adapt to new spatial and political configuration after the fall of the Empire, as well as the fronts of action developed by this ecclesiastical institution seeking its reorganization and consolidation, highlighting the figure of bishop Martin of Braga that was extremely active in this process.
The performance of bishop Martin of Braga in the organization of the Galicia church (second half - century VI)
Keywords: Martin of Braga; Popular Religiosity; Suebian Monarchy